The pharmacological modification of reperfusion injury with particular reference to calcium fluxes in the isolated rat heart - Du Toit, Eugene Francois (Division of Cardiology, 2018)
Myocardial reperfusion injury is thought to be caused by reperfusion induced i) cytosolic Ca²⁺ overload and/or, ii) the formation of oxygen derived freeradicals. At the start of this study, data implicating cytosolic Ca²⁺ overload in the genesis of reversible reperfusion injury were inconclusive. Although several workers have approached this problem by measurements of cytosolic calcium ions, it was my aim to examine the potential sources of such calcium overload. The experiments reported in this thesis were therefore designed to examine the role of altered intracellular and transsarcolemmal Ca²⁺ fluxes in the genesis of reperfusion stunning and arrhythmias. The study was also aimed at elucidating the possible sources and entry pathways contributing to this proposed cytosolic Ca²⁺ overload. In order to investigate the possible role of altered reperfusion Ca²⁺ fluxes in reperfusion injury, we exposed the isolated working, and Langendorff perfused rat heart model to ischaemia and reperfusion to induce reperfusion stunning and arrhythmias. Hearts were pre-treated (before ischaemia) or reperfused with pharmacological compounds, or by interventions known to enhance or inhibit intracellular or transsarcolemmal Ca²⁺ fluxes. The severity of reperfusion stunning (mechanical dysfunction) was measured by reperfusion aortic output, coronary flow and left ventricular pressure. The incidence of reperfusion ventricular arrhythmias was measured by the incidence of ventricular tachycardia and/ or fibrillation. In selected studies, the metabolic status of hearts was evaluated using biochemical assays performed on myocardial tissue samples. Data obtained in these studies indicate that increased Ca²⁺ fluxes through sarcolemmal L-type Ca²⁺ channels during early reperfusion exacerbate stunning, while inhibition of these fluxes with the Ca²⁺ antagonist drug nisoldipine or by Mg²⁺ or Mn²⁺ improve reperfusion function. These data also suggest that although interventions increasing Ca²⁺ fluxes early in reperfusion exacerbate reperfusion stunning, these same interventions improve reperfusion function when performed later. The data also indicate that Ca²⁺ may enter the myocyte indirectly via activation of the Na⁺/H⁺ and Na⁺/Ca²⁺ exchanger during reperfusion. Inhibition of Na⁺/H⁺ exchange activity by HOE 694 during reperfusion attenuated reperfusion stunning and arrhythmias. Both activation of the Na⁺/H⁺ (and Na⁺/Ca²⁺) exchanger and Ca²⁺ influx via the Ca²⁺ channel could contribute to reperfusion induced Ca²⁺ overload and subsequent injury. The study also showed that altered intracellular Ca²⁺ oscillations play a role in reperfusion stunning and arrhythmias as shown by the use of the SR Ca²⁺ release channel blocker, ryanodine. Inhibition of the sarcoplasmic reticulum Ca²⁺ A TP-ase pump by two novel inhibitors, thapsigargin and cyclopiazonic acid, during ischaemia and early reperfusion improved reperfusion function and reduced the incidence of ventricular arrhythmias. function when unphysiologically high concentrations of the peptide were infused into the heart during reperfusion. Taken together, these data suggest that: 1) Ca²⁺ fluxes during early reperfusion (intracellular and transsarcolemmal) play a role in reperfusion injury, 2) that both the Ca²⁺ channel and Na⁺/H⁺ exchange activity contribute to reperfusion injury by possibly contributing to cytosolic Ca²⁺ overload and that, 3) altered intracellular Ca²⁺ oscillations through the SR play a role in both stunning and arrhythmias. Thus the proposal is that modulation of Ca²⁺ fluxes through either the sarcolemma or the sarcoplasmic reticulum, lessen reperfusion injury (stunning and arrhythmias). Although these data do not provide direct evidence of reperfusion Ca²⁺ overload, they support the concept that calcium ions play a role in the genesis of reversible reperfusion injury.